Predicting breast cancer treatment response and prognosis using AI-based image classification - Wang, Bingyi; Chen, Shu; Li, Wei (Frontiers in Oncology, 2025)
IntroductionAccurate prediction of treatment response and prognosis in breast cancer patients is critical to advance personalized medicine and optimize therapeutic decision-making. Within the context of AI-enabled healthcare, there remains a pressing need to develop robust, interpretable models that can account for the temporal complexity and heterogeneity inherent in longitudinal patient data.MethodsThis study proposes a novel framework designed to model patient-specific treatment trajectories using a dynamics-aware, deep sequence learning architecture. Aligned with the core themes of computational prognostics and precision therapy, our method addresses the challenges posed by variable patient responses, missing clinical records, and complex pharmacological interactions. Existing approaches, including conventional supervised learning and static classification models, often fall short in capturing the underlying temporal dependencies, multimodal data fusion, and counterfactual reasoning necessary for real-world clinical deployment. These limitations hinder generalizability, especially in scenarios where treatment outcomes are delayed or weakly annotated. In contrast, our approach integrates recurrent modeling, attention mechanisms, and uncertainty quantification to better capture the evolving nature of patient health trajectories. Moreover, we incorporate domain-informed regularization techniques and causal inference modules to improve interpretability and clinical relevance.Results and DiscussionBy learning temporal dynamics in a personalized manner, the proposed model enhances predictive performance while remaining sensitive to patient-specific variations and therapeutic regimens. Through extensive validation on real-world breast cancer cohorts, we demonstrate that our framework not only outperforms existing baselines but also provides actionable insights that can inform adaptive treatment planning and risk stratification.